Multifactorial patterns of low performance development in german elite athletes - Wiedenbrüg, Kati; Roffler, Andrea; Reichert, Lukas; Mutz, Michael; Zentgraf, Karen; Krüger, Karsten; Justus Liebig University Giessen (My University, 2025)
Introduction: Low performance development (LPD) has been related to several training-related, biological or psychosocial factors. However, there is still hardly any comprehensive research on its multifactorial nature. Tis study explored whether factors previously associated with LPD manifest as cross-disciplinary pattern combinations across such athletes. Methods: Cluster analyses were computed based on performance-related (speed and strength of the lower body), biological (ratio TNFα:IL10; fT3, leptin, insulin) and psychosocial (perceived social support; mental well-being) data from 62 of 296 elite athletes whose performance development was below the samples’ average range. Group comparisons were calculated for demographic, anthropometric, nutritional and sleep-related variables, as well as for additional psychosocial (critical life events; perceived stress) and biological (single infammatory markers) variables. Results: Six patterns were identifed, which could be described via domain-specifc characteristics (lower body dynamics and social support), via an interdisciplinary combination of factors (social support, mental well-being and/or lower body dynamics) or by no characteristic pattern at group level. Conclusion: In general, this study extends research on LPD and illustrates the limited validity of generalisations while emphasising the additional value of individualisation for athletes who drop behind their peers. Moreover, the identifed Patterns point to the limitations of taking a cross-disciplinary approach at group level
Keywords: ddc:796